Influence of Sex and Age on Carcass Traits and Adipose Tissue Deposition in Poultry - Karim, Salma B; Shaker, Ahmed S (American Journal of Biodiversity, 2026)
This study investigated the influence of sex and slaughter age on carcass traits, internal organ characteristics, and fat deposition in poultry under standardized production conditions. A total of 160 birds were evaluated across four slaughter ages (40, 50, 60, and 70 days) to assess growth performance and carcass composition. The results revealed significant sex-related differences in carcass characteristics. Female birds exhibited higher live body weight (180.20 g) compared to males (163.98 g; p < 0.001). However, males demonstrated superior lean tissue deposition, with significantly higher thigh (18.41 vs. 17.31 g; p < 0.05) and back weights (14.99 vs. 13.07 g; p < 0.001). In terms of internal organs, females showed higher liver (4.36 vs. 2.34 g) and gizzard weights (3.64 vs. 2.73 g), whereas males exhibited markedly higher abdominal fat deposition (6.08 vs. 0.45 g; p < 0.001). Slaughter age significantly affected carcass performance. Birds at 60 days recorded the highest body weight (179.43 g), while the greatest carcass yield was observed at 50 days (106.79 g; p < 0.001). Breast weight peaked at 50 days (31.21 g), whereas no consistent age-related pattern was observed for abdominal fat, with the highest value at 60 days (4.69 g). Internal organ weights remained largely unaffected by age, except for minor variations in giblets (p < 0.01). In conclusion, both sex and age significantly influence carcass composition and fat deposition. Optimizing slaughter age (50–60 days) and considering sex-specific growth patterns can improve lean yield and production efficiency in commercial poultry systems.